The development of a modified 2 pair Dichotic Digit test recorded in a South African English Accent - Segoneco, Selekisho (Department of Health and Rehabilitation Sciences, 2021)
The impact of Central Auditory Processing Disorders (CAPD) on language and communication of children and adults is well documented in research. Several tests and normative data exist to assess and diagnose for CAPD, but these tests are not valid for use in South Africa due mismatch in the language or accent of the test recording and the language spoken in South Africa as well as normative data that were collected in the United States of America. As such CAPD may remain undiagnosed, misdiagnosed or designed management plans may be inappropriate as they arose from invalid tests. This study employed a developmental study design in order to adapt an existing 2-pair dichotic digit test (2-pair DDT) to a South African English accent to better suit the South African context. The study further investigated the effect of accent on dichotic digit test performance by comparing the performance of South African adults on the newly adapted South African accent 2-pair DDT and the existing 2-pair DDT, specified by the Department of Veteran Affairs (DVA), using a Wilcoxon-signed ranked test. Lastly, the study collected normative data for the 2-pair DDT that can be used in South Africa. The study successfully used a developmental study design to produce a South African accent 2-pair DDT that meets the international specifications as outlined by the DVA. A Wilcoxon signed ranked test showed that South Africans performed better on the South African accent 2- pair DDT than on the DVA specified test. The latter finding was supported by qualitative reports from the participants who found the DVA specified 2-pair DDT stimuli to be more difficult to listen to as compared to the South African accent test. Furthermore, the study produced preliminary normative data for the South African accent 2-pair DDT that met international standards and may be used to score 2-pair DDT performance. The successful use of the developmental study design to adapt the 2-pair DDT shows promising possibilities as a systematic process for adapting or developing tests that are more contextually appropriate for various contexts.